2012
DOI: 10.1371/journal.pone.0048276
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Linkage Analyses to Identify Genes That Influence Varroa Sensitive Hygiene Behavior in Honey Bees

Abstract: Varroa mites (V. destructor) are a major threat to honey bees (Apis melilfera) and beekeeping worldwide and likely lead to colony decline if colonies are not treated. Most treatments involve chemical control of the mites; however, Varroa has evolved resistance to many of these miticides, leaving beekeepers with a limited number of alternatives. A non-chemical control method is highly desirable for numerous reasons including lack of chemical residues and decreased likelihood of resistance. Varroa sensitive hygi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 96 publications
4
101
0
1
Order By: Relevance
“…They agreed with Rothenbuhler's (1964) conclusion that independent genetic loci regulate each component of hygienic behavior. Tsuruda, Harris, Bourgeois, Danka, and Hunt (2012) located candidate genes associated with the removal of mite-infested pupae observed in the resistance trait varroa sensitive hygiene (VSH). Studies on the heritability of VSH concluded that selective breeding can probably intensify its expression (Boecking, Bienefeld, & Drescher, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They agreed with Rothenbuhler's (1964) conclusion that independent genetic loci regulate each component of hygienic behavior. Tsuruda, Harris, Bourgeois, Danka, and Hunt (2012) located candidate genes associated with the removal of mite-infested pupae observed in the resistance trait varroa sensitive hygiene (VSH). Studies on the heritability of VSH concluded that selective breeding can probably intensify its expression (Boecking, Bienefeld, & Drescher, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In order to enable marker assisted selection (Rinderer, Harris et al, 2010), QTL studies of the hygienic behavior of the Minnesota Hygienic (Lapidge, Oldroyd et al, 2002; Oxley, Spivak et al, 2010) and the Varroa Sensitive Hygiene stocks (Tsuruda, Harris et al, 2012) have been conducted. Additional QTL studies have targeted mite grooming behavior (Arechavaleta-Velasco, Alcala-Escamilla et al, 2012) and mite reproductive success (Behrens, Huang et al, 2011).…”
Section: Implications For Selective Breeding For Honey Bee Healthmentioning
confidence: 99%
“…However, the QTL studies of Varroa resistant stocks have not yielded consistent QTL and show no overlap with transcriptome analyses (Le Conte, Alaux et al, 2011; Tsuruda, Harris et al, 2012). A tighter control of breeding and the identification of causative SNPs may increase the prospects for consistent findings in honey bee health research and enable marker assisted selection.…”
Section: Implications For Selective Breeding For Honey Bee Healthmentioning
confidence: 99%
“…The mechanisms underlying the genetic differences in the eastern Varroa-resistant bees remain unclear. Quantitative trait loci mapping techniques have been used to study gene expression, identify resistance genes (Parker et al, 2012), and identify chromosomal regions that contain genes influencing specific traits in resistant and susceptible A. mellifera lines (Behrens et al, 2012;Tsuruda et al, 2012). However, these studies used different breeding lines.…”
Section: Introductionmentioning
confidence: 99%